BATAS PARLEMEN PERLIAMENTARY THRESHOLD & PRESIDENTIAL THRESHOLD DI INDONESIA DALAM PRINSIP DEMOKRASI & HAM - Humairo, Putri Rummana; Ruslie, Ahmad Sholikhin (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
According to article 22 E paragraph (2) of the 1945 Constitution, elections are carried out on the basis of fairness to elect people’s representatives which are held every 5 years, in elections there is a parliamentary threshold to achieve democratic government, the purpose of holding elections is that citizens have the right to vote to elect representatives. the people in representative institutions at the government level in order to convey the aspirations of the people, in order to create fair competition, the implementation of elections must be better in each period, the formulation of the problems discussed are 1. Is the Presidential Threshold Perliamentary in accordance with a democratic perspective? 2. Is the MK decision No 48/PUU-XIX/2021 in accordance with the principles of democracy? The method used is reform-oriented research with a statute approach as well as a conceptual approach. Based on the analysis of legal material carried out, it is concluded that the Parliamentary Threshold & Presidential Threshold Limits in Indonesia are a form of democracy in the multiparty system that exists in Indonesia which is the content of democracy for public participation in the general election process to help determine the figure and direction of quality government leadership